Sentences and clauses in Jan Neruda’s Tales of the Lesser Quarter: a stylometric analysis - Schacherl, Martin (Bohemistyka, 2026)
The study provides a quantitative syntactic analysis of Jan Neruda’s Povídky malostranské (Tales of the Lesser Quarter) and seeks to empirically verify the traditional literary-historical characteristics of his style. Using stylometric indicators, it examines sentence length, the ratio of simple sentences to compound sentences, the relationship between the narrator and the characters, the degree of parataxis and hypotaxis, and the horizontal structure of the text. The results demonstrate the stability of Neruda’s syntactic model across the collection. Parataxis is the dominant principle, while hypotaxis serves more as a means of semantic differentiation. The differences between simple sentences and compound sentences are mainly quantitative in nature. The horizontal division of the text does not manifest itself as a factor of syntactic fragmentation, but rather as a means of compositional organisation and thematic clarity. The stylometric data thus corrects the idea of the fragmentary nature of Neruda’s syntax and confirms its structural coherence.